KEBUTUHAN BELAJAR REMAJA PUTUS SEKOLAH DI RW 005 CIPTA KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Dwimalini, Shintia; Natuna, Daeng Ayub; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on needs learn teenagers drop out of school in RW 005 Cipta Karya Kecamatan Tampan Kota Pekanbaru. The learning needs are diverse, so everyone tends to have different learning needs. Learning needs can be defined as a distance between the level of knowledge, skills, and attitudes that are owned at a time and want to obtain someone who can only be achieved through learning activities. Formulation problems research is how high the learning needs of teenagers drop out of school in RW 005 Cipta Karya Kecamatan Tampan Kota Pekanbaru? How much the indicator contributes to the learning needs of teenagers drop out of school in RW 005 Cipta Karya Kecamatan Tampan Kota Pekanbaru? And is there any difference in demographic factor of respondents to the learning needs. The purpose of this research is find to know the level of learning needs of teenagers drop out of school, to find out the large contribution of indicators to the learning needs of teenagers dropping out of school in RW 005 Cipta Karya Kecamatan Tampan Kota Pekanbaru and to find out the differences between each respondent's demographic factors for learning needs. Population in this study as many as 37 people. the researcher take all of it for the research sample by using technique sampling jenuh (all populations are sampled). Trials were conducted on 20 teenagers who were another place. An instrument data collection namely poll with 54 a statement and if the trial live 44 a statement that valid to make instrument in research. there are 10 items that invalid , and researchers throw all that is not valid, so that the whole instrument expressed reliabel as Cronbach Alpha = 0,963. The findings of the research indicated that the learning need teenagers drop out of school in RW 005 Cipta Karya Kecamatan Tampan Kota Pekanbaru is moderate.Key words: Needs Learn, Needs Learn Teenagers Drop Out Of School